International Publications on Radicalism and Terrorism in Indonesia: A Bibliometric Assessment - Munawar Fuad (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
This article analyses international publications on radicalism and terrorism in Indonesia in the Scopus database. This study employs a bibliometrics study to designate a set of quantitative methods of analysis of international scientific publications on radicalism and terrorism in Indonesia. Data was collected from search results in the Scopus database with a combination keyword